Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.ajic.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a negative pressure isolation space within a skilled nursing facility to control SARS-CoV-2 transmission

Abstract: Highlights Negative pressure isolation space is an effective method to meet needed surge capacity during the COVID-19 pandemic and future pandemics Planning for how and where to rapidly create a negative pressure isolation space is needed in congregate living areas such as skilled nursing facilities This demonstration shows the feasibility of using low-cost and in-house systems to quickly create negative pressure within a skilled nursing facility hallway a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 15 publications
0
55
0
2
Order By: Relevance
“…Our findings that staff at site A have high pre-existing seroprevalence (>40%) prior to intensive monitoring suggests this facility experienced a prior outbreak and had a level of herd immunity that limited spread of the virus from two positive staff members [44]. It is possible that other control measures and policies instituted at the time of monitoring, such as negative pressure isolation space [45], surveillance and monitoring systems and quarantine of positive staff [39,[46][47][48], environmental cleaning [49,50], and others [51], additionally contributed to protection against outbreaks. It is notable that at both sites, seroprevalence reached a maximum of 40% during the study period, suggesting this might correspond to a level of herd immunity when coupled with other preventative measures.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings that staff at site A have high pre-existing seroprevalence (>40%) prior to intensive monitoring suggests this facility experienced a prior outbreak and had a level of herd immunity that limited spread of the virus from two positive staff members [44]. It is possible that other control measures and policies instituted at the time of monitoring, such as negative pressure isolation space [45], surveillance and monitoring systems and quarantine of positive staff [39,[46][47][48], environmental cleaning [49,50], and others [51], additionally contributed to protection against outbreaks. It is notable that at both sites, seroprevalence reached a maximum of 40% during the study period, suggesting this might correspond to a level of herd immunity when coupled with other preventative measures.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated how large rooms or a group of rooms in a medical facility can rapidly be converted into isolation facilities by changing air flows [86][87][88][89][90][91]. In a skilled nursing facility in Lancaster, Pennsylvania, USA, an existing HVAC system was modified to minimise disease transmission between residents and staff and maintained an average pressure differential of −2.3 Pa (SD = 0.12 Pa) with the external hallway, and no transmission of SARS-CoV-2 between residents isolated to the space or transmission to the staff or other residents occurred [92].…”
Section: Increasing the Use Of Medical Or Surgical Masks And Hand Hygiene To Reduce The Transmission Of Respiratory Virusesmentioning
confidence: 99%
“…21 Diamond (2020). The first facility in Pennsylvania to accept COVID patients was much larger than average and had just built a negative pressure wing (Miller, et al 2020).…”
Section: Ivb Employees Of Duke Health and Meat Processors Before And After Prevention Protocolsmentioning
confidence: 99%